Identitas Budaya Jawa Pada Mural di Kampung Batik Kota Semarang - Erna Zuni Astuti; Arni Ernawati; Zainal Arifin (Jurnal Riset Komunikasi (JURKOM), 2023)
Mural is a creativity that is poured in the design of the walls of the building. Murals are large paintings created to support architectural spaces, so that murals cannot be separated from the elements that make up space, namely walls. Murals are one of the alternative media for visual arts that function as a forum for public aspirations through paintings with nuances of criticism, information on events, as well as a means of unifying conscience between artists and the community. Mural is a form of information and communication media for Visual Communication. The form of visual communication is the delivery of information or communication using images such as murals. In the city of Semarang, there is a village where every corner of the city is filled with beautiful murals. Of course, these murals have a function and purpose as a form of visual media communication. No exception as a visual cultural communication. In Kampung Batik Semarang, the walls and roads in the village are also decorated with beautiful murals and have meaning behind them. In this study, researchers will analyze and examine mural art in Kampung Batik Semarang as a visual media communication of Javanese culture. The researcher uses visual communication theory and identity theory. Mural art, which has been considered a mere creation of young people, turns out to have an innovative side to be developed to the maximum so that mural art is not only limited to pictures but also has meaning according to what is described. The purpose of this study is to see the meaning of Javanese identity in mural art in Kampung Batik. The meaning contained in the painting basically stores various information that will be conveyed indirectly.